THE SIGNIFICANCE AND PURPOSE OF ANCIENT MANUSCRIPT FOR THE NATIONâ€™S CULTURE AND CHARACTER DEVELOPMENT THROUGH THE HISTORY TEACHING - Saraswati, Ufi (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
The Indonesian nation conserves many ancient manuscripts. The ancient manuscripts are spread out throughout Indonesiaâ€™s archipelago, even though the total numbers of the ancient manuscripts in each area are not the same. The ancient manuscripts may be treated as documents of a nation, due to the fact that the documents may be referred to as writings containing pertinent information..Â Nowadays the teaching of history by utilizing ancient manuscripts are rarely conducted by teachers. However, it is necessary to have the efforts in comprehending the ancient manuscripts that any information of the pastÂ be passed to the current and future generations. The teaching of history based on scarce resources presents certain challenges to the teacher. In this country, history has been one of the core subjects in the curriculum, since elementary school, which leads to the question whether the teaching of history has been well operated?Â In fact, the teaching of history in many schools is merely the transferring the teacherâ€™s knowledge to the students in class through one-way communications. The students have become passive objects that have the duties to memorize notes given by the teacher in order to respond to the questions that will be examined. This type of history teaching method has caused the history subject uninteresting. A successful method of teaching history shall be by constructing a â€˜historical memoryâ€™ along with an â€˜emotional memoryâ€™. The study of ancient manuscript on history teaching is one of the many methods that can instigate â€œemotional memoryâ€. After students are provided with facts of history to construct â€œhistorical memoryâ€ in class, the emotional memory can be delved due to the study of ancient history.Â VariousÂ alternative methods in relation to the modification of history teaching are necessary to be developed. One of the methods that can be implemented is the capitalization of ancient manuscript for the History teaching, particularly for the development of the Nationâ€™s Culture and Character.